P471 Real-world experience of using Tofacitinib in Ulcerative Colitis in biologic naïve and biologic exposed patients. (21st January 2022) - Cheesbrough, J; Quraishi, M N; Sharma, N; Nassar, I
Abstract: Background: Tofacitinib is an oral, small molecule, which recently received NICE approval for the treatment of moderate to severe treatment refractory ulcerative colitis (UC). We present data on the regional experience for it use in relation to its efficacy in a cohort of patients with UC. Methods: This study analysed a retrospective, cohort from a large IBD unit in the UK. Patients with UC commenced on tofacitinib between 2019 and 2021 for active disease were included. Clinical disease activity was assessed at baseline, week 8, week 16 and during follow up visits. We evaluated clinical response (>50% reduction in symptoms) at week 8, proportion of patients requiring extended of induction therapy to week 16 and need for re-escalation of maintenance dosing. Results: A total of 55 patients were included (median age 34 years; IQR 15.75). Twenty six (47.3%) patients had pancolitis, 20 (36.4%) were biologic naïve and 18 (32.7%) were exposed to more than one biologic. Eighteen patients (32.7%) entered clinical response at week 8 and were able to de-escalate to 5mg BD maintenance therapy. Six patients (10.9%) had a primary non response and required a switch to an alternative biologic or a colectomy. Of the patients given an extended induction period (10mg BD for 16 weeks), 7/31 (22.6%) were able to de-escalate to 5mg BD, 15/31 (48.4%) continued on 10mg BD as maintenance and 9/31 (29.0%) discontinued treatment due to lack of clinical response. Of the patients on 5mg BD as maintenance 10/24 (41.6%) required re-escalation to 10mg BD maintenance dosing following a median duration of 10 weeks. Primary non response to tofacitinib were similar in biologic naïve patients compared to biologic exposed patients (25% vs 28.5% respectively). Biologic exposed patients were more likely to need 10mg BD as maintenance dosing compared to biologic naïve patients (72% vs 46.7% respectively). Conclusion: Consistent with prior literature, our experience confirms the effectiveness of Tofacitinib in both biologic naive and biologic exposed patients with moderate to severe UC with similar clinical response between the two cohorts. Patients exposed to biologics however appear to have a greater likelihood of escalation to 10mg BD for maintenance therapy.